[PP.12.18] RETINAL CAPILLARY RAREFACTION IN PATIENTS WITH UNTREATED MILD-MODERATE HYPERTENSION. (September 2016) - Jumar, A.; Harazny, J.M.; Ott, C.; Kistner, I.; Friedrich, S.; Wojtkiewicz, J.; Schmieder, R.E.
Abstract : Objective: Microvascular rarefaction influences peripheral vascular resistance, perfusion and metabolism by affecting blood pressure and flow pattern. In hypertension microvascular rarefaction has been described in experimental animal studies as well as in capillaroscopy of skin and biopsies of muscle tissue in patients. Retinal circulation mirrors cerebral microcirculation and allows non-invasive investigations. The aim of this study is to compare capillary rarefaction of retinal vessels in hypertensive versus normotensive subjects. Design and method: The study cohort consisted of 134 male and female patients with hypertension stage 1 or 2 and 55 male and female healthy people. All patients were non-smoker. Retinal vascular parameters were measured in perfusion image, non-invasively and in vivo by scanning laser Doppler flowmetry (Heidelberg Engineering, Germany). Capillary rarefaction was assessed by capillary area (CapA) (in pixel-number) and intercapillary distance (ICD) (in μm). Additionally retinal capillary flow (RCF) was measured. Results: ICD was greater in the hypertensive group (23.1 ± 5.8 μm vs 20.1 ± 4.2 μm, p = 0.001) compared to healthy individuals. Hypertensive patients showed less CapA compared to healthy people (1556 ± 649 vs 1821 ± 652, p = 0.013). Accordingly, RCF was significantly lower in the hypertensive group compared to the healthy control group (291 ± 71 AU vs 314 ± 61 AU, p = 0.018). Our data indicate a lower level of retinal capillary density in hypertensive patients. Conclusions: Patients with hypertension stage 1 or 2 showed retinal capillary rarefaction in comparison to healthy normotensive subjects.